MODERN APPLICATION OF FLUOR-CONTAINING PLANT EXTRACTS IN THE PREVENTION OF DENTAL DISEASES - Z.K. Khakimova; I.Yu. Mamatova (Journal of modern medicine, 2026)
The use of fluoride-containing medicinal plants in combination with local, inexpensive raw materials is a promising direction for the development of inexpensive dental prophylaxis. Objective: to describe the plant composition of a combined aqueous extract made from Salvia officinalis L., Thymus vulgaris L., Spinacia oleracea L., Urtica dioica L., and Melissa officinalis L., used for tooth enamel prevention, and to compare its cost with standard fluoride-based prophylactic methods. The combined plant extract is a biologically active, locally sourced, and cost-effective additive for tooth enamel prevention, requiring further standardization of its fluorine and polyphenol content.